Need analysis of basketball tactical instrument: A literature review - Soleh Solahuddin; Iman Sulaiman; Bambang Kridasuwarso; Samsudin Samsudin; Tengku Fadilah Tengku Kamalden (Sriwijaya Journal of Sport, 2023)
This study was conducted to analyse the need for a basketball tactical knowledge instrument. This study used a literature study or literature review, analysing 8 scientific journals which were published in Scopus-indexed publications and published no later than 2015 and most recently 2023. This study was conducted by making analyses and conclusions on journals related to research objectives. Several studies which were analysed in this study show the importance of tactical skills in basketball and the strengths and weaknesses of previous existing tactical skill instruments. It can be concluded that an accurate and easy-to-use instrument to measure tactical knowledge is needed. A practical instrument which related to game performance and can adjust all levels of basketball play is an important aspect of tactical knowledge identification and players’ development. This study is expected to be the foundation for future research related to instruments that can measure the tactical ability of basketball athletes without restrictions on age and level of play.